Veterinary Viewpoints, Summer 1983 - New York State College of Veterinary Medicine; Redmond, Karen (New York State College of Veterinary Medicine, 1983)
Topics in this issue include: Peregrination [Peregrine (falcon) Fund]; Post-DVM Career Choices Expand With Support; Memorial Gift Program Benefits All; 1983 Graduation; Pets & Poisonous Plants; In The Land of Araby; Footnotes: Wasserman to Head Physiology At Cornell (Robert H. Wasserman); New Grants & Awards (Donald Wassom, Joanne F. Fortune, Gary M. Dunny, Drew Noden); Terrier Field Day.